Surgical management of hepatic hydatid cysts – conservative versus radical surgery. Issue 10 (October 2020) - Deo, Kunal B.; Kumar, Rahul; Tiwari, Govinda; Kumar, Hemanth; Verma, Ganga R.; Singh, Harjeet
Abstract: Background: Surgical management is considered one of the effective treatment modality for liver hydatid. However the choice of surgery is debatable. This study aims to compare the outcome of radical surgery (RS) and conservative surgery (CS) in liver hydatid disease. Methods: This is retrospective analysis of prospectively maintained institutional data of surgically treated liver hydatid from January 2012 to January 2019. The basis of diagnosis was typical imaging, confirmatory Hydatid serology and/or Intraoperative details. The clinical presentation, radiological data, operative detail, post-operative outcome, post-operative recurrence data was analysed. Results: Sixty-four patients underwent surgery during the study period and were included. RS was done in 27 (42.2%) patients and CS in 37 (57.8%) patients. The mean age was 35.6 (13–72) years. The mean size of the cyst was 10.3 ± 2.9 cm. The cyst location was peripheral in 81.5% and 56.8% in RS and CS groups respectively. Intraoperative Cyst biliary communication was detected in 48.1% of RS & 35.1% in CS group of patients. The post-operative bile leak was significantly less in RS group (7.4% vs 27.0%, p = 0.047). Postoperative endoscopic stenting for persistent biliary fistula was necessitated in five of CS and only one patient from RS group. None of RS patients had recurrence while 3 patients of CS developed recurrence. Conclusion: Radical surgery reduces post-operative bile leak and prevents recurrence and may be preferable to conservative surgery.